2022
DOI: 10.3389/fgene.2022.1034892
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 rs1997623 variant and adult metabolic syndrome—Assessing the association in three ethnic cohorts of Arabs, South Asians and South East Asians

Abstract: Background: Animal and cell model studies have implicated CAV1 in the pathophysiology of metabolic disorders. Our previous studies demonstrated a potential association of CAV1 rs1997623 C/A variant with pediatric metabolic syndrome (MetS) in Arab children. In the present study, we evaluate whether the CAV1 variant associates with MetS Arab adults as well. The association signal is further examined for ancestry-specific variation by considering cohorts of other ethnicities.Method: The CAV1 rs1997623 was genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Little is known about CAV1 regulation in adipocytes; single nucleotide polymorphisms (SNPs) in the CAV1 gene have been associated with metabolic syndrome (MetS), which is a major risk factor for diabetes and coronary artery disease. Several CAV1 SNPs were found to be associated with MetS, including rs926198 in Caucasians and Hispanics [ 11 ], rs3807989 in Han Chinese [ 12 ], rs11773845 in Latin Americans [ 13 ], rs3807992 in Persians [ 14 ], and rs1997623 in Kuwaiti children, as shown in our previous study [ 15 ], and as found in another adult population [ 16 ]. Although central obesity is a landmark trait for the diagnosis of MetS, the full spectrum of traits relating to MetS includes various other metabolic factors related to hypertension, diabetes, and dyslipidemia.…”
Section: Introductionsupporting
confidence: 66%
“…Little is known about CAV1 regulation in adipocytes; single nucleotide polymorphisms (SNPs) in the CAV1 gene have been associated with metabolic syndrome (MetS), which is a major risk factor for diabetes and coronary artery disease. Several CAV1 SNPs were found to be associated with MetS, including rs926198 in Caucasians and Hispanics [ 11 ], rs3807989 in Han Chinese [ 12 ], rs11773845 in Latin Americans [ 13 ], rs3807992 in Persians [ 14 ], and rs1997623 in Kuwaiti children, as shown in our previous study [ 15 ], and as found in another adult population [ 16 ]. Although central obesity is a landmark trait for the diagnosis of MetS, the full spectrum of traits relating to MetS includes various other metabolic factors related to hypertension, diabetes, and dyslipidemia.…”
Section: Introductionsupporting
confidence: 66%
“…Overall, this Research Topic collected four articles ( Al Madhoun et al, 2022 ; Cullina et al, 2023 ; James et al, 2023 ; Sezgin and Kaplan, 2022 ).…”
mentioning
confidence: 99%
“…Thus, this Research Topic presents a series of research works on population-specific variation in human diseases ( Al Madhoun et al, 2022 ; Cullina et al, 2023 ; James et al, 2023 ; Sezgin and Kaplan, 2022 ). The complementary Research Topic in Frontiers in Genetics named “High-throughput Sequencing-based Investigation of Chronic Disease Markers and Mechanisms, Volume II” ( https://www.frontiersin.org/research-topics/53085/high-throughput-sequencing-based-investigation-of-chronic-disease-markers-and-mechanisms-volume-ii ) continues the collection of articles on the markers of human diseases ( Orlov et al, 2022 ).…”
mentioning
confidence: 99%